Three‐dimensional lithospheric S wave velocity model of the NE Tibetan Plateau and western North China Craton. Issue 8 (31st August 2017) - Wang, Xingchen; Li, Yonghua; Ding, Zhifeng; Zhu, Lupei; Wang, Chunyong; Bao, Xuewei; Wu, Yan
Abstract: We present a new 3‐D lithospheric V s model for the NE Tibetan Plateau (NETP) and the western North China Craton (NCC). First, high‐frequency receiver functions (RFs) were inverted using the neighborhood algorithm to estimate the sedimentary structure beneath each station. Then a 3D V s model with unprecedented resolution was constructed by jointly inverting RFs and Rayleigh wave dispersions. A low‐velocity sedimentary layer with thicknesses varying from 2 to 10 km is present in the Yinchuan‐Hetao graben, Ordos block, and western Alxa block. Velocities from the middle‐lower crust to the uppermost mantle are generally high in the Ordos block and low in the Alxa block, indicating that the Alxa block is not part of the NCC. The thickened crust in southwestern Ordos block and western Alxa block suggests that they have been modified. Two crustal low‐velocity zones (LVZs) were detected beneath the Kunlun Fault (KF) zone and western Qilian Terrane (QLT). The origin of the LVZ beneath the KF zone may be the combined effect of shear heating, localized asthenosphere upwelling, and crustal radioactivity. The LVZ in the western QLT, representing an early stage of the LVZ that has developed in the KF zone, acts as a decollement to decouple the deformation between the upper and lower crust and plays a key role in seismogenesis. We propose that the crustal deformation beneath the NETP is accommodated by a combination of shear motion, thickening of the upper‐middle crust, and removal of lower crust. Key Points: A new 3‐D V s model for NE Tibet and western Northern China Craton is constructed Multiple processes contributed to the crustal deformation in NE Tibet Western Alxa block and southwestern Ordos block have been modified